Diagnostic Stability of Major Depressive Disorder in hospitalized patients in a University Hospital: a Brief Report - Enrique De Doménico; João Mauricio Castaldelli-Maia; Antonio Ventriglio; Julio Torales (Medicina Clínica y Social, 2021)
Introduction: There may be a discordance between diagnoses at admission and discharge of mentally ill patients with major issues regarding their diagnostic stability. The objective of this brief report was to determine the diagnostic stability of major depressive disorder at patients’ discharge and if the diagnosis of their hospital admission had been retained. Methodology: This was a pilot, descriptive, cross-sectional, and retrospective observational study. A non-probabilistic sampling of consecutive cases was used.  We reviewed the medical records, at admission and discharge, of patients with an initial diagnosis of major depressive disorder, hospitalized in the Department of Psychiatry of the ‘Hospital de Clínicas’ of the National University of Asunción, Paraguay, during the months of October to December 2020. Results: Fifty-three patients with a diagnosis of major depression on their hospital admission were included in the study (mean age = 35.7 ± 16.5 years). 79.2 % were women, 52.8 % were single, and 37.7 % were from the Central province of Paraguay. The most frequent diagnosis at discharge was borderline personality disorder, in 35.8% of cases. Major depressive disorder was confirmed in 15.1% of cases. No significant relationship was found between any discharge diagnosis and sociodemographic data. Conclusion: The results of this study, although preliminary, described the trajectories of diagnoses in the Psychiatry Department of a University hospital, but confirmatory studies are needed.